Historicizing the Lived Experience of Violence: Bryen's Violence in Roman Egypt. Issue 3 (June 2015) - Grey, Cam
<x xml:space="preserve">Abstract</x> <mixed-citation id="lsi12145-cit-0001" publication-type="book" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink"> <string-name> <surname>Bryen</surname>, <given-names>Ari Z.</given-names></string-name> <year>2013</year>. <source content-type="bookTitle">Violence in Roman Egypt: A Study in Legal Interpretation</source>. <publisher-loc>Philadelphia, PA</publisher-loc>: <publisher-name>University of Pennsylvania Press</publisher-name>. Pp. <fpage>376</fpage>. $75.00 cloth; $75.00 eBook. </mixed-citation> Ari Byren's Violence in Roman Egypt: A Study in Legal Interpretation (2013) effectively inserts itself into two complementary fields of inquiry and discussion within the field of classical studies. First, it offers a detailed treatment of the social history of small communities in Roman Egypt, providing an important contribution to the study of violence in antiquity—a topic that has gained interest in recent years. Second, it is an extended meditation on the place of violence within a society and law's role in defining and eliminating it.